Chlorophytum (Asparagaceae) of Uganda—a molecular phylogenetic approach and the resurrection of Chlorophytum elgonense Bullock - Matovu, Paul; Ballesteros, Jesus Adrian Chimal; Namaganda, Mary; Nordal, Inger; Bjorå, Charlotte S. (Phytotaxa, 2025)
Species of Chlorophytum in Uganda were studied using molecular analyses and scanning electron microscopy of the seed surfaces. The four floral regions of Uganda were surveyed in 2019 and 2020 in known localities for Chlorophytum as well as putative new localities. One nuclear (ITS), and 5 chloroplast regions (trnL-F spacer, trnL intron, rps16 intron, rpl20-5’rps12 and psbA-trnH) were PCR-amplified and sequenced. Phylogenetic analyses followed Maximum Likelihood and Bayesian inference. Morphometric data were acquired from the collected vouchers guided by a character list of the most informative characters. Chlorophytum elgonense, recorded as a synonym for C. comosum in the Flora of Tropical East Africa, has been reinstated at the rank of species. The species, C. longifolium, was recorded for the first time in Uganda. The postulated sister species relations of C. occultum to C. alismifolium and C. hirsutum to C. andongense are disputed.